INTERNAL COMMUNICATION OF THE ORGANIZATION IN THE EMPLOYEE MUTATION PROCESS OF THE DIRECTORATE GENERAL OF CUSTOMS AND EXCISE IN 2024 - Irsan Febriansyah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to examine internal organizational communication in the employee transfer process at the Directorate General of Customs and Excise in 2024. This topic is important because employee transfers are an integral part of organizational dynamics and human resource management strategies. However, in practice, the process still raises various communication issues, such as delays in information delivery, unclear transfer patterns, and the emergence of anxiety and speculation among employees. This study employed a qualitative approach with a descriptive case study method. Data were collected through in-depth interviews with four executive employees who experienced transfers in 2024 and one informant from the personnel administration section, supported by observation and document analysis. The findings show that internal communication in the transfer process at the Directorate General of Customs and Excise is dominated by formal downward communication through decrees, official memoranda, and announcements in internal organizational media. However, this communication pattern tends to be one-way and does not adequately accommodate upward communication, resulting in limited opportunities for employees to express their aspirations, perceptions, and needs. In contrast, horizontal communication among colleagues functions relatively well and supports the adaptation process of transferred employees, particularly through the sharing of work experience, technical knowledge, and social support in the new work environment. From the perspective of the organizational socialization model, the transfer process has not been fully supported by open, participatory, and well-planned communication across the stages of anticipation, encounter, and metamorphosis. Transferred employees tend to seek information through direct questioning, disguised conversations, and observation of their new work environment. These findings confirm that the effectiveness of employee transfers is strongly influenced by the quality of internal organizational communication. Therefore, the Directorate General of Customs and Excise needs to develop a more transparent, two-way, fair, and well-structured communication pattern in the transfer process so that transfers are no longer perceived as a form of punishment, but rather as part of career development and organizational capacity building.